Security Brokerage Markets under Price Uncertainty - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1992)
This paper develops a model of security broker behavior under price uncertainty. The model examines the process of matching orders and the determinants of equilibrium brokerage commission rates. Institutional arrangements, search efficiency, execution costs, volume, risk, and the unit price of the security are shown to affect equilibrium brokerage commission rates. Some stylized facts of security brokerage are explained.